Tisztességtelen kereskedelmi gyakorlatok – végrehajtás és gyakorlat az Európai Unióban - Tárczy, Edit Zsuzsanna (Debreceni Jogi Műhely, 2012)
The first aim of this paper is to show the rules of the 2005/29/EC Directive on unfair commercial practices (hereafter: UCPD) on enforcement and the rules of the Member States of the EU on enforcement. The second aim is to show some cases on unfair commercial practices (from the European Court of Justice (hereafter: ECJ) and from national organizations too). This time „enforcement” means only „practice”, so this paper won’t deal with control or supervisory activity.At the first point there are the rules on enforcement from the UCPD and some rules of some Member States. At the second point there are the decisions of the ECJ. First, there are the decisions in connection with the implementation and the harmonization. Second, there are the decisions in connection with the rules of the UCPD and advertising. At the third point there are the decisions of the national organizations in connection with the UCPD. At the fourth point there are the decisions of the national organizations in connection with advertising.